A potent tilapia secreted granulin peptide enhances the survival of transgenic zebrafish infected by Vibrio vulnificus via modulation of innate immunity. Issue 75 (April 2018) - Wu, Sheng-Han; Lin, Hong-Jie; Lin, Wen-Fu; Wu, Jen-Leih; Gong, Hong-Yi
Abstract: Progranulin (PGRN) is a multi-functional growth factor that mediates cell proliferation, survival, migration, tumorigenesis, wound healing, development, and anti-inflammation activity. A novel alternatively spliced transcript from the short-form PGRN1 gene encoding a novel, secreted GRN peptide composed of 20-a.a. signal peptide and 41-a.a. GRN named GRN-41 was identified to be abundantly expressed in immune-related organs including spleen, head kidney, and intestine of Mozambique tilapia. The expression of GRN-41 and PGRN1 were further induced in the spleen of tilapia challenged with Vibrio vulnificus at 3 h post infection (hpi) and 6 hpi, respectively. In this study, we established three transgenic zebrafish lines expressing the secreted GRN-41, GRN-A and PGRN1 of Mozambique tilapia specifically in muscle. The relative percent of survival (RPS) was enhanced in adult transgenic zebrafish expressing tilapia GRN-41 (68%), GRN-A (32%) and PGRN1 (36%) compared with control transgenic zebrafish expressing AcGFP after challenge with V. vulnificus . It indicates tilapia GRN-41 is a potent peptide against V. vulnificus infection. The secreted tilapia GRN-41 can induce the expression of innate immune response-related genes, such as TNFa, TNFb, IL-8, IL-1β, IL-6, IL-26, IL-21, IL-10, complement C3, lysozyme (Lyz) and the hepatic antimicrobial peptide hepcidin ( HAMP ), in adult transgenic zebrafish without V. vulnificus infection. The tilapia GRN-41 peptide can enhance the innate immune response by further elevating TNFb, IL-1β, IL-8, IL-6, and HAMP expression in early responsive time to the V. vulnificus challenge in transgenic zebrafish. Our results suggest that the novel GRN-41 peptide generated from alternative splicing of the tilapia PGRN1 gene is a potent peptide that defends against V. vulnificus in the transgenic zebrafish model by modulation of innate immunity. Highlights: An alternatively spliced transcript of the short-form PGRN1 gene encoding a novel secreted granulin peptide GRN-41 was identified in tilapia. The PGRN1 and GRN-41 transcripts of tilapia PGRN1 gene were both further induced in the spleen of tilapia after challenged with Vibrio vulnificus. The survival rate was highly enhanced in adult transgenic zebrafish expressing secreted tilapia GRN-41 after challenged with V. vulnificus . The novel tilapia GRN-41 peptide is a potent peptide that defends against V. vulnificus in the transgenic zebrafish model by modulation of innate immune-related genes.